Modeling and simulation of InAs photodiode on electric field profile and dark current characteristics - Roslan P.S.A.; Ker P.J.; Ahmad I.; Pasupuleti J.; Fam P.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dark currents; Electric fields; Electron tunneling; Epitaxial growth; Imaging techniques; Infrared radiation; Metallorganic vapor phase epitaxy; Molecular beam epitaxy; Organometallics; Photodiodes; Electric field profiles; Electrical characteristic; Generation recombination; High electric fields; III-IV semiconductors; InAs; Metal-organic vapor phase epitaxy; Trap assisted tunneling; Narrow band gap semiconductors